TOURISM DEVELOPMENT OF KAMPUNG LAWANG SEKETENG SURABAYA CITY - Faisea Faisea; Susi Hardjati (DIA: Jurnal Administrasi Publik, 2021)
The research conducted is based on the phenomenon of the Kampung Lawang Seketeng Tourism Object which has a historical tourist attraction because there are many historical relics in the form of buildings and historical objects in the Tourism Object. In addition, this village is known for its two great Indonesian hero figures, namely Bung Karno and Bung Tomo. Therefore, there is a need for continuous development to make the tourism of Kampung Lawang Seketeng better. The purpose of this research is to describe the tourism development of Kampung Lawang Seketeng, Surabaya city. This research uses qualitative research methods by collecting data in the form of interviews, documentation, and data analysis. The location of the research was conducted in the Tourism Object of Kampung Lawang Seketeng, Surabaya City. The results of the research obtained are (1) The development of a tourist attraction in the tourism object of Kampung Lawang Seketeng is adequate (2) The development of facilities and services for the tourism object of Kampung Lawang Seketeng is available but is still inadequate in the aspect of parking space. (3) Development of easy access to reach the tourist attraction of Kampung Lawang Seketeng is adequate in terms of road access. However, the direction signs are still inadequate. (4) The development of additional services at the tourist attraction of Kampung Lawang Seketeng is adequate. However, it is lacking in the aspect of hygiene due to the lack of awareness of the surrounding community.